The Development of the Growth Mindset of the Eleventh Grade Students Using Open Approach - Nisreen Puteh; Singha Prasitpong; Kasem Premprayoon (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to develop the growth mindset of eleventh-grade students using Open Approach. Six students from grade 11 from a school under the Yala Secondary Educational Service Area Office were selected. The students initially had a fixed mindsetat levels F1 and F2 and a weak growth mindset at level G1 before the development process. This study is a classroom action research. The instruments of this research consisted of three lesson plans on probability using Open Approach, activity sheets, a mindset assessment form, an interview form, a post-lesson report, a video camera, and a voice recorder. Data analysis was conducted using the mindset framework analysis from the Mindset Works Educator Kit (2012). Percentage analysis and qualitative methods were obtained in the research. The research findings indicated that students who participated in learning through Open Approach showed progress in their growth mindset scores, with 33% reaching level G3, 50% reaching level G2, and 17% remaining at level G1. Students showed behaviors of embracing challenges, demonstrating efforts, solving problems independently, valuing peer feedback as beneficial to learning, and viewing others' success as a source of inspiration and learning examples.